Employee Engagement in A Remote Working Scenario - Anand, Ashwini Anoor; N. Acharya, Sheetal (Universitas Prasetiya Mulya, 2021)
Remote working is a concept in which the employees do not commute or travel to the Organizations place of work but allows the employees to work outside of the traditional office environment. Employee engagement can be viewed as an attitude of an employee/employeeâ€™s a to be productive, to excel and therefore be committed towards the organisation. Remote working applies to a variety of employees especially office or desk-based workers. This paper explores different facets of the remote workerâ€™s persona and provides recommendations and practices to enhance employee engagement of the employees working remotely. Remote work culture is not a new concept, but due to the current Covid-19 Pandemic situation there seems to be a rapid shift of many employees to the remote working model essentially working away from the traditional office ecosystem. This paper examines two aspects of working remotely, a. In regular times b. during a crisis and in both these scenarios how to keep the remote workers engaged and motivated to ensure a minimum if not zero loss of Productivity.Â https://doi.org/10.21632/irjbs.14.2.119-127